2002
DOI: 10.1038/sj....bjc.6600207...
|View full text |Cite
|
Sign up to set email alerts
|

Role of proteolytic enzymes in human prostate bone metastasis formation: in vivo and in vitro studies

Abstract: Prostate cancers ability to invade and grow in bone marrow stroma is thought to be due in part to degradative enzymes. The formation of prostate skeletal metastases have been reproduced in vitro by growing co-cultures of prostatic epithelial cells in bone marrow stroma. Expression of urokinase plasminogen activator, matrix metalloproteinase 1 and 7 by prostatic epithelial cells were identified using immunocytochemistry. Also, in vivo tissue sections from human prostatic bone marrow metastases were stained. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…A likely candidate proteolytic enzyme able to cleave perlecan was MMP-7 or matrilysin. MMP-7 expression and activity have been well linked to cancer and PCa, specifically (Cardillo et al, 2006; Hart et al, 2002; Hashimoto et al, 1998; Lynch et al, 2005; Powell et al, 1993). MMP-7 has many demonstrated ECM substrates including collagen I, III, IV, V, fibronectin (Woessner and Taplin, 1988), vitronectin (Imai et al, 1995), and aggrecan (Fosang et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A likely candidate proteolytic enzyme able to cleave perlecan was MMP-7 or matrilysin. MMP-7 expression and activity have been well linked to cancer and PCa, specifically (Cardillo et al, 2006; Hart et al, 2002; Hashimoto et al, 1998; Lynch et al, 2005; Powell et al, 1993). MMP-7 has many demonstrated ECM substrates including collagen I, III, IV, V, fibronectin (Woessner and Taplin, 1988), vitronectin (Imai et al, 1995), and aggrecan (Fosang et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Protein expression of MMP-7 and its inhibitor, tissue inhibitor of metalloproteinase-1 (TIMP-1), reveals a higher MMP-7 to TIMP-1 ratio in more advanced PCa versus localized PCa or benign prostatic hyperplasia, indicating that the enzyme is active in invasive PCa tissue (Hashimoto et al, 1998). Interestingly, immunohistochemistry studies showed increased MMP-7 stromal deposition in high grade PCa and bone marrow metastatic lesions (Cardillo et al, 2006; Hart et al, 2002). When transfected with MMP-7, DU-145 PCa cells showed enhanced invasiveness after intraperitoneal injection into immunodeficient mice (Powell et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-three genes were more highly expressed in omentum compared to ovary, and 33 genes were more highly expressed in ovary compared to omental metastasis. At least 20/56 (36%) genes differentially expressed between ovary and omentum (P , 0.01) have previously been implicated in metastasis, cell motility, migration, and cytoskeletal function and include ANGPT1 (14) , MMP1 (15) , CSPG2 (16) , MAPT (17) , DPT (18) , KIAA1775 (19) , F2RL2/PAR3 (20) , PCDH9 (19) , ADAM22 (21) , TBX1 (22) , EVPL (23) , GPR135 (24)(25)(26) , CDC2 (27) , POLYDOM (28) , CAMK2G (29) , CCL19 (30) , DLX2 (31) , PPAP2C (32) , SAG (33) and HMGI-C (35) . Ten of 56 (18%) genes that were differentially expressed between ovary and omentum (P , 0.01) have gene network relationships with the p53 tumor suppressor gene and include MJD/ATX3 (35,36) , STAR (36)(37)(38) , NEF3 (39,40) , NR1H4 (40)(41)(42) , EVPL (43)(44)(45) , TMPO (45,46) , PIR51 (45,47,48) , APOBEC2 (49) , MMP1 (50) , and CDC2 …”
Section: Genes Exhibiting Differential Expression Between Ovaries Andmentioning
confidence: 99%
“…A reduction of the invasive and metastatic phenotype has been obtained by down-regulating the expression of the uPA gene or inhibiting its enzymatic activity [9,[23][24][25]. uPA overexpression is associated with the more aggressive prostate cancer cell lines and is constitutively secreted by bone homing prostate cancer cell lines, such as PC3 [9,21,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Metastases are usually seen in metaphysis, where PCa cells form close contact with osteoblasts or BMSC [6,7]. PCa adapt and eventually proliferate in this environment [8][9][10][11]. Our understanding of the underlying mechanism is incomplete; but evidence has been obtained both for paracrine interactions mediated by soluble factors, and for cell-to-cell contact.…”
Section: Introductionmentioning
confidence: 99%